THE PRIORITIES OF SHAHABEDDIN SUHRAWARDY’S VIEWS ON YOUTH EDUCATION AND UPBRINGING - Gularo Rakhimova Ibragimovna (Galaxy International Interdisciplinary Research Journal, 2023)
This article provides information about the priority directions of Shahabeddin Suhrawardy’s views on youth education and training. Although Shahabeddin Suhrawardy focused primarily on metaphysics and spirituality in his works, he put forward certain considerations and ideas related to the education and upbringing of young people.